The effectiveness of immersed in extract viscera of sea cucumber Holothuria sp on growth, consumption level and feed efficiency in tilapia larvae Oreochromis niloticus - Andi Aliah Hidayani; Marlina Achmad; Dody Dharmawan Trijuno; Jitima Suwanmala; Alifah Nurul Jannati; Atira Rewa; A. Dyar Fadya Auliah (Jurnal Akuakultur Indonesia, 2025)
The aim of this research was to determine the effect of sea cucumber immersion extract on growth, consumption and feed efficiency in masculinized tilapia larvae aged six to seven days. September–November 2022 was the time the research was carried out and the experimental method used in this study was a Completely Randomized Design (CRD) with five treatments and three replications. The treatment used was the soaking of sea cucumber viscera with doses of 0 ml/L (A), 1 ml/L (B), 3 ml/L for 24 hours (C), 5 ml/L for 24 hours (D), and 0.5 ml/L 17α-MT for 12 hours as positive control (E), then maintained for 60 days. Parameters observed included absolute length growth, absolute weight growth, feed consumption level, feed efficiency and water quality. The results showed that immersion sea cucumber innards for 24 hours with a dose of 1 ml/L showed the highest growth rate in absolute length and a dose of 3 ml/L showed the highest feed consumption rate.